Kuat Tekan Beton Hvfa Di Air Gambut - Sopian, Sopian; Ismeddiyanto, Ismeddiyanto; Olivia, Monita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
High Volume Fly Ash (HVFA) is a concrete with green building concept. The quantity of fly ash each year increases as coal production increases. HVFA Concrete offers a short-term solution of the growing need for portland cement. Concrete with the use of pozzolanic material has better strength in reducing the effect of organic acid from peat water than Ordinary Portland Cement (OPC). This research examines the compressive strength of OPC concrete and HVFA concrete exposed in peat water environment with a variation of fly ash as many as 50% of the weight of the cement volume. Concrete samples were made with a cylindrical mold with a height of 210 mm and a diameter of 105 mm. The number of samples made in this study was 18 pieces. The OPC and HVFA culinder concrete were cured for 28 days. Later, the specimens were put in a container and cure with peat water for 7 and 28 days. The results of fresh concrete test showed that the greater the amouny of fly ash used in concrete mix, the workability decreased. For the case of specimens immersed in peat water for 28 days, its concrete strength was 31,05% higher than that of immersed in fresh water. Based on the results of these tests it was concluded that HVFA concrete was able to reduce peat acid attack compared to OPC concrete.Keywords: HVFA, compressive strength, peat environment